THE ROLE OF ANGIOTENSIN AT1 RECEPTORS IN THE DIURETIC, NATRIURETIC, KALIURETIC AND BLOOD-PRESSURE RESPONSES INDUCED BY ANGIOTENSIN-II ACTIVATION OF THE MEDIAN PREOPTIC NUCLEUS IN CONSCIOUS RATS - Ferreiradovale, C.; Renzi, Antonio [UNESP]; Camargo, GPA; Saad, W. A.; Luiz, A. C.; Menani, José Vanderlei [UNESP]; Silveira, JEN; Camargo, LAA (Associação Brasileira de Divulgação Científica (ABRADIC), 1995)
We determined the effects of two classical angiotensin II (ANG II) antagonists, [Sar(1), Ala(8)]-ANG II and [Sar(1), Thr(8)]-ANG II, and losartan (a nonpeptide and selective antagonist for the AT 1 angiotensin receptors) on diuresis, natriuresis, kaliuresis and arterial blood pressure induced by ANG II administration into the median preoptic nucleus (MnPO) of male Holtzman rats weighing 250-300 g. Urine was collected in rats submitted to a water load (5% body weight) by gastric gavage, followed by a second water load (5% body weight) 1 h later. The volume of the drug solutions injected was 0.5 mu l over 10-15 s. Pre-treatment with [Sar(1), Ala(8)]-ANG II (12 rats) and [Sar(1), Thr(8)]-ANG II (9 rats), at the dose of 60 ng reduced (13.7 +/- 1.0 vs 11.0 +/- 1.0 and 10.7 +/- 1.2, respectively), whereas losartan (14 rats) at the dose of 160 ng totally blocked (13.7 +/- 1.0 vs 7.6 +/- 1.5) the urine excretion induced by injection of 12 ng of ANG II (14 rats). [Sar(1), Ala(8)]-ANG II impaired Na+ excretion (193 +/- 16 vs 120 +/- 19): whereas [Sar(1), Thr(8)]-ANG II and losartan blocked Na+ excretion (193 +/- 16 vs 77 +/- 15 and 100 +/- 12, respectively) induced by ANG II. Similar effects induced by ANG II on K+ excretion were observed with [Sar(1), Ala(8)]-ANG II, [Sar(1), Thr(8)]-ANG II, and losartan pretreatment (133 +/- 18 vs 108 +/- 11, 80 +/- 12, and 82 +/- 15, respectively). The same doses as above of [Sar(1), Ala(8)]-ANG II (8 rats), [Sar(1), Thr(8)]-ANG II (8 rats). and losartan (9 rats) blocked the increase in the arterial blood pressure induced by 12 ng of ANG II (12 rats) (32 +/- 4 ru 4 +/- 2, 3.5 +/- 1, and 2 +/- 1: respectively. The results indicate that the AT1 receptor subtype participates in the increases of diuresis, natriuresis. kaliuresis and arterial blood pressure induced by the administration of ANG II into the MnPO.
Keywords: ANGIOTENSIN II; LOSARTAN; DIURESIS; NATRIURESIS; KALIURESIS; BLOOD PRESSURE; MNPO